2014
DOI: 10.1115/1.4027142
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analysis of Flow Phenomena in a Centrifugal Pump Operating Under Low Flow Rates

Abstract: The characteristics of flow instabilities as well as the cavitation phenomenon in a centrifugal pump operating at low flow rates were studied by experimental and numerical means, respectively. Specially, a three-dimensional (3D) numerical model of cavitation was applied to simulate the internal flow through the pump and suitably long portions of the inlet and outlet ducts. As expected, cavitation proved to occur over a wide range of low flow rates, producing a characteristic creeping shape of the head-drop cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…In Cs7, the intensity of vortices is observed around the periphery of cross sections and minimal at the core, this ensure the helicity (product of vorticity and velocity) at that section [25]. Even for end suction centrifugal pump, Fu et al [26] confirmed the presence of low frequency oscillation of inlet pressure near the impeller eye by means of fast response pressure transducers. Similar kind of cross sectional studies can be extended to other flow rates for more detailing of inlet pipe flow passage.…”
Section: Source Of Noise Across Cross Sections At 05qnmentioning
confidence: 79%
“…In Cs7, the intensity of vortices is observed around the periphery of cross sections and minimal at the core, this ensure the helicity (product of vorticity and velocity) at that section [25]. Even for end suction centrifugal pump, Fu et al [26] confirmed the presence of low frequency oscillation of inlet pressure near the impeller eye by means of fast response pressure transducers. Similar kind of cross sectional studies can be extended to other flow rates for more detailing of inlet pipe flow passage.…”
Section: Source Of Noise Across Cross Sections At 05qnmentioning
confidence: 79%
“…It is observed that angular distribution of pressure amplitude at f BPF exhibits a modulated pattern characterized by the presence of six local peaks and valleys. The modulation pattern is closely associated with rotor-stator interaction inside the model pump [22] and [23]. At off-design conditions, especially at flow rates of 0.2 Q d and 1.4 Q d , pressure amplitudes are much larger than that at the rated condition.…”
Section: Unsteady Pressure Pulsationsmentioning
confidence: 93%
“…Under part-load and overload conditions, the flow in centrifugal pumps is extremely unstable [2,3]. Unstable flow structures, such as return vortex at the tongue, shedding vortex at the blade trailing edge and return vortex at the inlet or outlet, will occur in centrifugal pumps when they are operated under part-load conditions [4][5][6]. The rotor-stator interaction at the tongue and the shedding vortex at the blade trailing edge are the main causes of unstable pressure pulsation in centrifugal pumps [7,8].…”
Section: Introductionmentioning
confidence: 99%